Complexes of oxoplatin with rhein and ferulic acid ligands as platinum(iv) prodrugs with high anti-tumor activity. Issue 5 (16th January 2020) - Tan, Ming-Xiong; Wang, Zhen-Feng; Qin, Qi-Pin; Zou, Bi-Qun; Liang, Hong
Abstract : The rhein Pt IV prodrug Pt3 induced apoptosis through the dysfunction of the mitochondria and displayed more effective inhibitory effects in vivo than cisplatin. Abstract : We herein designed two new Pt IV prodrugs of oxoplatin ( cis, cis, cis -[PtCl2 (NH3 )2 (OH)2 ]), [Pt IV Cl2 (NH3 )2 (O2 C-FA)2 ] (Pt-2 ) and [Pt IV Cl2 (NH3 )2 (O2 C-RH)2 ] (Pt-3 ), by conjugating with ferulic acid (FA-COOH) and rhein (RH-COOH) which have well-known biological activities. Three other Pt(iv ) complexes of [Pt IV Cl2 (NH3 )2 (O2 C-BA)2 ] (Pt-1 ), [Pt IV Cl2 (NH3 )2 (O2 C-CA)2 ] (Pt-4 ) and [Pt IV Cl2 (NH3 )2 (O2 C-TCA)2 ] (Pt-5 ) (where BA-COOH = benzoic acid, CA-COOH = crotonic acid and TCA-COOH = trans -cinnamic acid) were also prepared for the comparative study. Like most Pt IV prodrug complexes, the cytotoxicity of Pt-3 containing the biologically active rhein (RH-COOH) ligand against lung carcinoma (A549 and A549/DDP) cells was higher than those of Pt-1, Pt-2, Pt-4, cisplatin and Pt-5 . Moreover, the cytotoxicity of Pt-3 in HL-7702 normal cells was lower than those of Pt IV derivatives bearing BA-COOH, FA-COOH, TCA-COOH and CA-COOH ligands. The highly efficacious Pt-2 and Pt-3 were found to accumulate strongly in the A549/DDP cells, with the prodrug Pt-3 showing highest levels of penetration into the mitochondria. The prodrug Pt-3 effectively entered the A549/DDP cells and caused mitochondrial damage, significantly greater than Pt-2 . In addition, the prodrug Pt-3 exhibited higher antitumor efficacy (inhibition rates (IR) = 67.45%) than Pt-2 (28.12%) and cisplatin (33.05%) in the A549/DDP xenograft mouse model. Thus, the prodrug Pt-3 containing the rhein (RH-COOH) ligand is a promising candidate drug targeting the mitochondria.